2019
DOI: 10.15244/pjoes/87060
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Biostimulants on the Content of P, K, Ca, Mg, and Na in the Skin and Flesh of Potato Tubers

Abstract: The nutritional value of agricultural crops has to be closely monitored due to the continued decrease in the concentrations of minerals in fruit and vegetables in recent decades [1]. Potato tubers are a rich source of nutrients in the human diet, including protein, carbohydrates, fiber, antioxidants (vitamin C, phenols, anthocyanins), and minerals (1-2%) [2][3]. Ratios between minerals are of particular importance to human health [4]. The growing demand for potatoes with high nutritional value necessitates res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…High concentrations of some minerals in the skin may reflect direct uptake from the soil across the periderm [12]. Głosek-Sobieraj et al [13] showed that Kelpak SL increased K content and Bio-algeen S90 increased P content in the skin of tubers of medium-early potato cultivars. High concentrations of most minerals in the skin of potato tubers may reflect direct uptake from the soil across the periderm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of some minerals in the skin may reflect direct uptake from the soil across the periderm [12]. Głosek-Sobieraj et al [13] showed that Kelpak SL increased K content and Bio-algeen S90 increased P content in the skin of tubers of medium-early potato cultivars. High concentrations of most minerals in the skin of potato tubers may reflect direct uptake from the soil across the periderm.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of most minerals is higher in the skin than in the flesh of potato tubers [12]. Bio-algeen S90 increased P content in the skin and Mg content in the flesh, whereas Kelpak SL increased Ca content both in the flesh and in the skin and K content in the skin [13]. Other products based on A. nodosum extract Primo increased P and K content in potato tubers [14], and E. maxima extract Afrikelp LG-1 increased K, P, Ca, Mg, and Na content in potato leaves [15].…”
Section: Introductionmentioning
confidence: 95%
“…It was noted that in Experiment I, the increase in dry matter was most favorable after the application of 100% NPK and in Experiment II with full protection (Tables 1 and 2). Obtaining such an effect may have been due to a faster release of compounds and an increase in plant resistance to disease under the influence of microorganisms contained in UGmax [17][18][19].…”
Section: Dry Mattermentioning
confidence: 99%
“…Environmental and consumer protection prompts the search for new opportunities through simplifications in crop production or the use of various agents such as immune stimulants, bacterial vaccines, algae extracts and effective preparations containing microorganisms [10,[13][14][15][16]. Such substances include the soil conditioner UGmax, which, thanks to the microorganisms and elements contained in its composition, has the effect of processing, composting and humification of natural and organic fertilizers to create humus [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…and Paenbacillus spp. ), kelp extract, macro-and micronutrients: 9% N, 3%P 2 O 5 , 6% K 2 O, 0.6% Fe, 0.05% Mn and 0.05% Zn [42] Bactofil-A and Bactofil-B contain various combinations of Azospirillum brasilense, Azospirillum lipoferum, Azotobacter vinelandii, Bacillusmegaterium, Bacillus polymyxa, Bacillus circulans, Bacillussubtilis, Pseudomonas fluorescens, Streptomyces and plant growth hormones [43] Blatt Boden-Foliar a microbial solution that consists mainly of lactic acid bacteria: Lactobacillus casei (5 × 10 9 cfu mL −1 ) and Lactobacillus plantarum (5 × 10 9 cfu mL −1 ); photosynthetic bacteria: Rhodopseudomonas palustris (5 × 10 9 cfu mL −1 ); yeasts: Saccharomyces cerevisiae (5 × 10 3 cfu mL −1 ) and sugarcane molasses [44] UGmax N-1.2, P-0.2, K-2.9, Mg-0.1 g kg, Na-0.2, Mn-0.3 mg kg, lactic acid bacteria, photosynthetic bacteria, Azotobacter spp., Pseudomonas spp., yeasts, actinomycetes [37][38][39] Eko-U żyźniacz N-0.6, P-0.3, K-0.7 g kg, endomycorrhizal fungi, bacteria, earthworm fibrinolytic enzymes [37,39] Asahi SL (Atoniki and Chaloperone) 0.3% para-nitrophenol sodium salt, 0.2% ortho-nitrophenol sodium salt, 0.1% 5-nitroguaiacol sodium salt [6,40] Tytanit (Mg-Tytanit) 8.5 g Ti per1 dm 3 (0.8% m/m) in the form of Ti-ascorbate [21,45,46] AGRO-SORB Folium a growth stimulant containing 18 biologically active free amino acids (L-alpha) obtained via enzymatic hydrolysis (minimum 9.3% w/w or 100 g per 1000 mL): aspartic acid-0.450%, serine-0.321%, glutamate acid-1.814%, glycine-2.743%, histidine-0.208%, arginine-0.131%, threonine-0.323%, alanine-0.524%, proline-0.347%, cysteine-0.435%, tyrosine-0.174%, valine-0.551%, methionine-0.349%, lysine-0.661%, methionine-0.308%, leucine-0.180%, phenylalanine-0.218% and tryptophan-0.05% [47] Optysil contains silicon (16.8% SiO 2 ) and 2% chelated iron [48,49] Herbagreen contains silicon (17% SiO 2 ), calcium (36.7% CaO), magnesium (2.4% MgO), iron (3.4% Fe 2 O 3 ), titanium (0.5% TiO 2 ) and other ingredients [48] Stymjod concentrated liquid fertiliser produced with the use of the cold plasma nanotechnology. The product contains an optimal ratio of macronutrients (N-6.3%; P-4.58%; K-6.42%; Mg-1.69%; S-1.6%) and micronutrients (B-0.46%; Cu-0.17%; Fe-0.14%; Mn-0.16%; Mo-0.028%; Zn-0.42%) for plants, as well as humic and amino acids that increase plant resistance to unfavourable environmental conditions [50,51] Biostimulants are widely used in agriculture as seed dressing agents and foliar sprays during the growing season and harvest.…”
Section: Biostimulant Active Ingredientsmentioning
confidence: 99%